Engagement Planning, Bid Pricing, and Client Response in the Market for Initial Attest Engagements - Johnstone, Karla M.; Bedard, Jean C. (The Accounting Review, 2001)
This study examines how client risk factors and the provision of additional services affect engagement planning and bid pricing for a set of initial engagement proposals that a single firm submitted to its prospective clients in 1997–1998. We find little effect of risk on planned personnel hours, but show that the firm responds to fraud and error risk factors by applying engagement-planning strategies such as assigning more high-risk specialist personnel, assigning more industry expert personnel, applying more intensive testing, and/or performing additional review. Analyzing proposed fees while controlling for planned personnel hours, we find risk premia for both fraud and error risk factors. Supplemental analysis of accepted vs. rejected bids shows that the risk premia are detectable for bids accepted by clients (i.e., the engagements the firm will actually perform), implying that risk premia are not bid away in the market. We also find that for clients purchasing additional services, the firm plans more hours and uses industry experts more often. Results reveal a relatively small fee premium for additional services clients across all bids, but analysis of accepted vs. rejected bids implies that this premium is bid away in the market.